The practice and impact of divine healing in saint john apostolic faith mission : a missiological perspective - Kgatle, Mookgo S. (Scriptura, 2018)
Previous works on Saint John Apostolic Faith Mission have focused on the establishment of the church by its female founder, Christina Nku. Other works have studied the reasons that caused the church to undergo several schisms over the years. Some scholars have discussed Saint John Apostolic Faith Mission as a Pentecostal church instead of an African Independent Church. This article looks at the practice of divine healing in Saint John Apostolic Faith Mission and its impact on the growth of the church, by using a missiological lens. This shall be established by looking at the practice of divine healing in the African Independent Churches in general. The practice of divine healing in Saint John Apostolic Faith Mission shall be explored by looking at the role of the Holy Spirit, healing symbols and healing songs. The article also looks at the relationship between divine healing and western medicine. The purpose here is to demonstrate the impact of divine healing on the growth of Saint John Apostolic Faith Mission.